Improving the assessment and management of obesity in UK children and adolescents: the PROMISE research programme including a RCT - Russell M Viner; Sanjay Kinra; Deborah Christie; Tim J Cole; Silvia Costa; Helen Croker; Tam Fry; Yingfen Hsia; Lee Hudson; Anthony S Kessel; Steve Morris; Irwin Nazareth; et al. (Programme Grants for Applied Research, 2020)
Background: Five linked studies were undertaken to inform identified evidence gaps in the childhood obesity pathway. Objectives: (1) To scope the impact of the National Child Measurement Programme (NCMP) (study A). (2) To develop a brief evidence-based electronic assessment and management tool (study B). (3) To develop evidence-based algorithms for identifying the risk of obesity comorbidities (study B). (4) To conduct an efficacy trial of the Healthy Eating and Lifestyle Programme (HELP) (study C). (5) To improve the prescribing of anti-obesity drugs in UK adolescents (study D). (6) To investigate the safety, outcomes and predictors of outcome of adolescent bariatric surgery in the UK (study E). Methods: Five substudies – (1) a parental survey before and after feedback from the National Childhood Measurement Programme, (2) risk algorithm development and piloting of a new primary care management tool, (3) a randomised controlled trial of the Healthy Eating and Lifestyle Programme, (4) quantitative and qualitative studies of anti-obesity drug treatment in adolescents and (5) a prospective clinical audit and cost-effectiveness evaluation of adolescent bariatric surgery in one centre. Results: Study A – before the National Childhood Measurement Programme feedback, three-quarters of parents of overweight and obese children did not recognise their child to be overweight. Eighty-seven per cent of parents found the National Childhood Measurement Programme feedback to be helpful. Feedback had positive effects on parental knowledge, perceptions and intentions. Study B – risk estimation models for cardiovascular and psychosocial comorbidities of obesity require further development. An online consultation tool for primary care practitioners is acceptable and feasible. Study C – the Healthy Eating and Lifestyle Programme, when delivered in the community by graduate mental health workers, showed no significant effect on body mass index at 6 months (primary outcome) when compared with enhanced usual care. Study D – anti-obesity drugs appear efficacious in meta-analysis, and their use has expanded rapidly in the last decade. However, the majority of prescriptions are rapidly discontinued after 1–3 months of treatment. Few young people described positive experiences of anti-obesity drugs. Prescribing was rarely compliant with the National Institute for Health and Care Excellence guidance. Study E – bariatric surgery appears safe, effective and highly cost-effective in adolescents in the NHS. Future work and limitations: Work is needed to evaluate behaviour and body mass index change in the National Childhood Measurement Programme more accurately and improve primary care professionals’ understanding of the National Childhood Measurement Programme feedback, update and further evaluate the Computer-Assisted Treatment of CHildren (CATCH) tool, investigate delivery of weight management interventions to young people from deprived backgrounds and those with significant psychological distress and obtain longer-term data on anti-obesity drug use and bariatric surgery outcomes in adolescence. Trial registration: Current Controlled Trials ISRCTN99840111. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 8, No. 3. See the NIHR Journals Library website for further project information.